The answer is an integer.

Algebra Level 3

If x = 5 2 x=\sqrt{5}-2 , find the value of x 3 + 6 x 2 + 13 x + 10 x 3 + 6 x 2 + 9 x + 2 \large \frac{x^{3}+6x^{2}+13x+10}{x^{3}+6x^{2}+9x+2} .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Otto Bretscher
May 5, 2015

First we note that x + 2 = 5 x+2=\sqrt{5} and, cubing, x 3 + 6 x 2 + 12 x + 8 = 5 5 , x^3+6x^2+12x+8=5\sqrt{5}, or, x 3 + 6 x 2 = 5 5 8 12 x x^3+6x^2=5\sqrt{5}-8-12x . Now we can substitute x 3 + 6 x 2 + 13 x + 10 x 3 + 6 x 2 + 9 x + 2 = x + 2 + 5 5 3 x 6 + 5 5 = 6 5 2 5 = 3 \frac{x^3+6x^2+13x+10}{x^3+6x^2+9x+2}=\frac{x+2+5\sqrt{5}}{-3x-6+5\sqrt{5}}=\frac{6\sqrt{5}}{2\sqrt{5}}=3

Gustavo Milla
Jul 30, 2015

Noel Lo
May 26, 2015

x = 5 2 x = \sqrt{5} - 2

x + 2 = 5 x+2 = \sqrt{5}

( x + 2 ) 2 = ( 5 ) 2 (x+2)^2 = (\sqrt{5})^2

x 2 + 4 x + 4 = 5 x^2+4x+4 = 5

x 2 = 1 4 x x^2 = 1-4x

x 3 = x 4 x 2 x^3 = x-4x^2

Simplify the given expression to 1 + 4 x + 8 x 3 + 6 x 2 + 9 x + 2 = 1 + 4 x + 8 x 4 x 2 + 6 x 2 + 9 x + 2 = 1 + 4 x + 8 2 x 2 + 10 x + 2 1+\frac{4x+8}{x^3+6x^2+9x+2} = 1+\frac{4x+8}{x-4x^2 + 6x^2 + 9x+2} =1+ \frac{4x+8}{2x^2+10x+2}

= 1 + 4 x + 8 2 ( 1 4 x ) + 10 x + 2 = 1 + 4 x + 8 2 8 x + 10 x + 2 = 1 + 4 x + 8 2 x + 4 = 1 + 2 = 3 =1+\frac{4x+8}{2(1-4x) +10x+2} = 1+\frac{4x+8}{2-8x+10x+2} = 1+\frac{4x+8}{2x+4} = 1+2 = \boxed{3} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...